The dynamics of Public Transport in the Metropolitan Region of São Paulo: A demand perspective from 2017 to 2023 - Daroncho, Celio; Martinez, Pedro José Perez (Technical and Scientific Journal Green Cities, 2024)
Urban Public Transport is essential for urban mobility and the sustainability of cities. In March 2020, the Covid-19 Pandemic began, forcing the decree of quarantines and lockdowns in almost all cities in the world, facts that abruptly interrupted urban mobility, generating significant drops in the demand for transport in urban areas. In São Paulo, the quarantine began on March 24, 2020, and ended on August 17, 2021, significantly impacting not only the use of Urban Public Transport, but in the urban mobility. This study analyses the monthly and annual volumes of passengers transported by public transport systems in the Metropolitan Region of São Paulo between 2017 and 2023, using the tools of basic descriptive statistics, such as mean, median, amplitude, asymmetry, and kurtosis, in addition to the graphical analysis of the distribution of the data series. The data show that the drop in demand, except for subway transport, has occurred since 2018, with a significant drop in the Pandemic with a gradual resumption from the second half of 2020, with 2023 still below 2017 levels, on average 27% in the urban bus system, 16% in the metropolitan bus system, 8% in the subway system and 24% in the urban train system. This study shows an apparent accommodation of data at this new level, which can greatly impact not only the financial health of companies, but in the total urban mobility.